2014
DOI: 10.1038/nrurol.2014.196
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy as a modulator and target in prostate cancer

Abstract: Autophagy, or “self eating,” is an adaptive process that helps cells cope with metabolic, toxic, and even infectious stressors. While the adaptive capability of autophagy is generally beneficial, autophagy can also facilitate enhanced nutrient utilization and improved growth characteristics in cancer cells. Moreover, autophagy can promote greater cellular robustness in the context of therapeutic intervention. This has proven to be the case in advanced prostate cancer, where preclinical data largely supports th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
141
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(143 citation statements)
references
References 75 publications
1
141
0
1
Order By: Relevance
“…9,68 In clinical trials, EGFR-TKIs have been used to treat patients with lung cancer 9 and prostate cancer. 57 Although the combination of an anticancer agent with an autophagy inhibitor is designed to synergize cell death of cancer cells, 56,60,61 based on our findings, the same strategy might not be suitable for the combination of an EGFR-TKI and an autophagy inhibitor such as 3-MA or spautin-1. We found gefitinib or erlotinib increased autophagic flux promoting cell death.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…9,68 In clinical trials, EGFR-TKIs have been used to treat patients with lung cancer 9 and prostate cancer. 57 Although the combination of an anticancer agent with an autophagy inhibitor is designed to synergize cell death of cancer cells, 56,60,61 based on our findings, the same strategy might not be suitable for the combination of an EGFR-TKI and an autophagy inhibitor such as 3-MA or spautin-1. We found gefitinib or erlotinib increased autophagic flux promoting cell death.…”
Section: Discussionmentioning
confidence: 95%
“…[56][57][58][59][60][61][62] The downstream inhibitors of autophagy chloroquine and hydroxychloroquine suppress tumor growth in a laboratory mouse model 63 and have been used in clinical trials of human patients. 56,[59][60][61][62]64 In a clinical trial, the addition of chloroquine has significantly improved median survival of patients with glioblastoma receiving conventional chemotherapy and radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Although Zannah group suggested that HCQ in combination with the antidiabetic, biguanide drug metformin reduces blood glucose and lipid profile levels significantly in rats, clinically there are no interactions between HCQ and metformin [24,25]. Another interesting story based on their autophagy inhibiting property, recent several clinical studies suggest that CQ enhances the metformin-induced cell apoptosis and intensify the metformin-induced inhibition of cell proliferation of breast-and other cancers [26][27][28]. Reduced glucose levels or hypoglycaemia have also been reported with mefloquine and quinine [8,29].…”
Section: Antidiabeticsmentioning
confidence: 99%
“…A number of studies have suggested that CQ can inhibit autophagy through the prevention of lysosome acidification, and subsequently, the inhibition of autophagosome-lysosome fusion, to block the degradation of autolysosomes at the last step of autophagy (8,9). Previous studies have indicated that CQ exhibited an antitumor effect on several types of cancer, including glioblastoma (10,11), hepatocellular carcinoma (12), breast cancer (13), prostate cancer (14) and pancreatic cancer (15), which prompts us to hypothesize that CQ may be able to influence the growth of esophageal carcinoma through the modulation of autophagy. Therefore, the aim of the present study is to explore the antitumor effect of CQ on the esophageal squamous carcinoma cell line EC109, and the potential mechanism for this effect.…”
Section: Introductionmentioning
confidence: 99%